Tax Aggressiveness: A Meta Analysis in Agency Theory Perspective - Bani Alkausar; Mienati Somya Lasmana; Prinintha Nanda Soemarsono (Universitas Airlangga, 2020)
This study examines the phenomenon of corporate tax aggressiveness in Indonesia. The meta-analysis technique is used to find conclusions about the trends of similar research that have been studied. The sample of this study is 22 published articles for quantitative and qualitative analysis. The results of the meta-analysis show that corporate governance (independent commissioners, audit committees, and audit quality) and company characteristics (leverage, firm size, and profitability) influence tax aggressiveness. Significant statistical test results have not been able to provide conclusions regarding the phenomenon of tax aggressiveness, because there is no researcher who clearly explains which agency theory is used to explain the phenomenon of research. Agency theory includes whole participant relations in business. It is necessary to have a clear agency theory identification so that there is no mistake in determining the solution to the problem under study. Error making theory as a basis for problem solving in research will lead to problem solving that is not appropriate. Researchers have a tendency not to convey research results that are inconsistent or insignificant with previous studies. This is why meta-analysis techniques are difficult to use.